2017
DOI: 10.1111/1754-9485.12584
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife radiosurgery for brain metastases from gastrointestinal primary

Abstract: Colorectal cancer metastases tend to have a higher rate of leptomeningeal failure than other types of GI cancer metastases. Radiosurgical management of brain metastases from GI primary represents an acceptable management option. Neurologic death remains problematic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 21 publications
1
8
0
1
Order By: Relevance
“…Similar to other studies, we demonstrated that the OS is better for patients with KPS ≥ 70 from the univariate analysis (31,32). Xiaoyu et al showed that the OS increased for patients with a favourable KPS score from univariate and multivariate analyses (42).…”
Section: █ Conclusionsupporting
confidence: 90%
“…Similar to other studies, we demonstrated that the OS is better for patients with KPS ≥ 70 from the univariate analysis (31,32). Xiaoyu et al showed that the OS increased for patients with a favourable KPS score from univariate and multivariate analyses (42).…”
Section: █ Conclusionsupporting
confidence: 90%
“…Several retrospective studies on SRS treatment for BMs from GI cancer have been reported. However, patient numbers in these reports were relatively small [1,2,4,5].…”
Section: Introductionmentioning
confidence: 94%
“…Gastrointestinal (GI) cancer rarely metastasizes to the brain. Particularly, brain metastases (BMs) from esophageal and gastric cancers are much less common than colorectal cancer BMs [1][2][3][4][5]. However, due to the currently widespread use of magnetic resonance (MR) imaging with gadolinium enhancement, BMs are being detected ever more frequently.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations